2021
DOI: 10.1097/mlr.0000000000001433
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal Hormone Therapy and Suicide in a National Sample of Midlife and Older Women Veterans

Abstract: Background: Among midlife and older women, menopause symptoms and menopausal hormone therapy have been linked to mental health disorders and other comorbidities related to suicide. However, the role of hormone therapy as a prognostic factor of suicide risk is largely unknown. Objectives: To examine associations between menopausal hormone therapy, suicide attempts, and suicide among midlife and older women Veterans. Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Moreover, it also revealed that oral estradiol stimulated thyrotropin-releasing hormone to induce the secretion of TSH ( 38 ). At the same time, a large sample study on the relationship between menopausal hormone therapy and suicide risk in middle-aged and older women showed that hormone therapy increased the risk of suicide attempts by 1.4-fold ( 39 ). Currently, the percentage of women is 76.30% (90/118) among suicide attempters, accounting for a large proportion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it also revealed that oral estradiol stimulated thyrotropin-releasing hormone to induce the secretion of TSH ( 38 ). At the same time, a large sample study on the relationship between menopausal hormone therapy and suicide risk in middle-aged and older women showed that hormone therapy increased the risk of suicide attempts by 1.4-fold ( 39 ). Currently, the percentage of women is 76.30% (90/118) among suicide attempters, accounting for a large proportion.…”
Section: Discussionmentioning
confidence: 99%
“…Our study seems to be the first nationwide observational study that has followed up women who initiate HT for clinically verified depression in time-to-event analyses. However, a recent cohort study 49 followed up 291 709 US women older than 50 years for 4.5 years and found that HT was associated with a 2 times higher risk of suicide, which may be an indicator of severe depression. A review from 2015 including 19 experimental studies on the effect of systemically administered HT for developing depressive symptoms in women without depression 17 provided no support for an effect of oral or transdermal estrogen alone or combined with progestin on mood in nondepressed women.…”
Section: Discussionmentioning
confidence: 99%
“…However, androgen deprivation therapy has been linked to increased insomnia symptoms ( Savard et al, 2013 ). Of particular relevance to the current review, menopausal hormone therapy has been linked to increased risk of suicide attempt and increased risk of death by suicide in a large-scale sample of midlife and older veterans ( Gibson et al, 2021 ).…”
Section: Sexual and Gender Minority People And Sleepmentioning
confidence: 99%